Immediate effect of electrical vestibular stimulation on autonomic and respiratory parameters and reaction time in patients with Parkinson’s disease - Asha G; Varun Manjunath; Karthik N; Yashica Gowda R; Sai Sailesh Kumar Goothy; Rohit Singh Chouhan; Anitha Lakshmi (Asian Journal of Medical Sciences, 2025)
Background: Both the electrical and natural vestibular stimulation were reported to alter both the blood pressure and motor output of respiration. After a thorough review of the literature, the studies observed the immediate effect of vestibular stimulation on autonomic and respiratory functions is sparse. Hence, the present study was undertaken. Aims and Objectives: The present study was undertaken to observe the immediate effect of electrical vestibular stimulation on autonomic and respiratory parameters in patients with Parkinson’s disease (PD). Materials and Methods: The present study recruited 30 patients with PD after obtaining written informed consent. After recording the baseline values, a single session of stimulation was administered to the participants and soon after recorded the participants. Blood pressure was recorded by Diamond BPDG 141 Deluxe Multicolor LED Mercury Free BP Monitor. Pulse rate and respiratory rate were recorded manually. Auditory and visual reaction times were recorded using the RT apparatus. Results: There was a significant decrease in the systolic (P=0.011) and diastolic blood pressure (P=0.002) after the stimulation. The pulse rate was decreased significantly (P=0.071) followed by the vestibular stimulation. No change in the respiratory rate was observed followed by the vestibular stimulation. There was a significant decrease in the visual reaction time for red (P=0.0087) and green light (P=0.0007), as a result of the intervention. Auditory reaction time for low pitch (P=0.0056) was significantly decreased followed by the intervention. Conclusion: The study results support that a single session of electrical vestibular stimulation has beneficial effects on blood pressure and reaction time in patients with PD. Further detailed studies are recommended with long-term administration of electrical stimulation to recommend the use of electrical vestibular nerve stimulation in the management of non-motor symptoms in PD patients.